Toxicity, deficiency and dysmetabolism of trace elements in Ghanaian clinically stable schizophrenics - Asare, G.A.; Tetteh, R.; Amedonu, E.; Asiedu, B.; Doku, D. (Macedonian Journal of Medical Sciences, 2014)
AIM: The purpose of the study was to determine the levels of Copper (Cu), selenium (Se), Zinc (Zn), Lead (Pb) and Lithium (Li) in patients in Accra and Pantang Psychiatric Hospitals in Ghana since no data exist. SUBJECTS AND METHODS: Simple random sampling of age-matched subjects was used to recruit 81 schizophrenics and 25 mentally healthy controls in 2012. Serum levels of Cu, Se, Zn, Pb and Li were determined by flame atomic absorption spectroscopy (FAAS). RESULTS: Mean levels were as follows: Cut 766 ± 250 μg/L and Cuc 855 ± 270 μg/L (p = 0.168). Set 149 ± 72 μg/L and Sec 108 ± 61 μg/L (p=0.009). Znt 702 ± 438 μg/L and Znc 1007 ± 593 μg/L (p = 0.028). Pbt 1.38 ± 0.05 μg/L and Pbc 0.10 ± 0.05 μg/L (p = 0.000). Li levels for the test group (Lit) was 4077 ± 2567 μg/L, whiles that of the controls was undetectable < 0.02 μg/L. Se, Pb and Li levels were significantly higher in schizophrenic patients compared to controls. While Zn and Cu levels were lower in the same group. CONCLUSION: Trace elements dysmetabolism exist among Ghanaian schizophrenics and monitoring is essential to avoid the adverse effects of metal overload or deficiency. © 2014 Asare et al.
Keywords: Accra; Dysmetabolism; Psychiatric patients; Schizophrenia; Trace elements